PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA PEGAWAI DINAS PERTANIAN KOTA BIMA - Syahruddin Syahruddin; Amir Tengku Ramly; Lidwina Sri Ardiasih (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
An organization that is advanced and competitive is an organization that always runs the wheels of the organization well, and pays attention to and fixes the slightest problem in the organization to find a solution. Satisfaction or dissatisfaction in the organization as a reflection of the comparison or gap between what is expected and the reality obtained. Satisfaction will be felt by employees. The purpose of this study was to analyze the influence of leadership style, organizational culture and position promotion on job satisfaction of the employees of the Bima City Agriculture Office. As input for the preparation of programs and activities within the Bima City Agriculture Office. Between the dependent variable and the independent variable. The population of this study were all civil servants serving at the Bima City Agriculture Service as many as 119 people. The sample approach in this study was a probability approach and used arandom sampling techniquewith the Slovin formula so that the number of research samples was 34 people. The research instrument is a questionnaire that uses a Likert scale. The data is then analyzed with multiple linear regression. The results of the study provide empirical evidence that: (1) Leadership style has no significant and significant effect on employee job satisfaction, meaning that high job satisfaction does not depend on the superior's leadership style; (2) Organizational culture has no significant effect on employee job satisfaction: (3) Position promotion has a positive and significant effect on employee job satisfaction at the Department of Agriculture of the City of Bima. Therefore, as an effort to increase job satisfaction, it is necessary to have a professional promotion without being judged on the basis of proximity alone.